The Impact of Labeling Effect and Social Media Marketing on Consumer Purchasing Decisions and Loyalty at Super Indo Supermarket Malang - Fahmi, Syaifuddin; Indarwati, Peni; Az Zahra, Dita Aulia (Universitas Negeri Gorontalo, 2025)
Purpose: To analyze in depth the impact of labeling effect on purchasing decisions and its implications on consumer loyalty, analyze in depth the impact of social media marketing on purchasing decisions and its implications on consumer loyalty, and analyze in depth the impact of purchasing decisions on consumer loyalty at Super Indo Supermarket Malang, to be able to solve problems related to the National Research Master Plan (RIRN) on the theme of economics and human resources with the focus areas of PRN Social Humanities, Education, Arts, and Culture on the topics of entrepreneurship, cooperatives and MSMEs.Design/Methodology/Approach: The study was conducted on 200 respondents who were met directly at Super Indo Supermarket Malang, while the research respondents were selected by accidental sampling. The collected data were then analyzed using the Structural. Equation Modeling - Partial Least Square (SEM-PLS) method. Where the data obtained from the distribution of questionnaires will be analyzed by looking at and considering the results of the outer model, inner model, and examination of the mediation model.Findings: The results of the study show that the labeling effect has a significant influence on consumer purchasing decisions and loyalty. While on the other hand, social media marketing also influences consumer purchasing decisions and loyalty. There is a mediating role of the purchasing decision variable that connects the labeling effect variable and Social Media Marketing to Loyalty.